The Clash of Liberties: Religious Freedom, Human Rights, and the Ascendance of Christian Nationalism in the United States - Kusumawikan, James William (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
The guarantee of religious freedom enshrined in the United States Constitution, intended to protect the diverse religious beliefs of its citizens, has inadvertently spawned unforeseen consequences. This article examines how the noble principle of religious freedom has intersected with the rise of Christian nationalism, posing a significant threat to democracy and human rights within the nation. Despite the Constitution's emphasis on individual liberties, the emergence of Christian nationalism has fueled a divisive narrative that privileges certain religious identities over others, thereby undermining the foundational principles of equality and pluralism. Through an analysis of historical contexts, legal frameworks, and contemporary socio-political dynamics, this article explores the complex interplay between religious freedom, human rights, and the encroachment of Christian nationalism on democratic norms. It sheds light on the challenges posed by this paradoxical situation and underscores the urgent need for safeguarding both religious freedom and human rights within the United States' democratic framework. Keywords: Religious freedom, US Constitution, Christian nationalism, Democracy, Human rights, Pluralism, Socio-political dynamics. Jaminan kebebasan beragama yang diabadikan dalam Konstitusi Amerika Serikat, yang dimaksudkan untuk melindungi beragam keyakinan agama warga negaranya, telah secara tidak sengaja menimbulkan konsekuensi yang tidak terduga. Artikel ini mengkaji bagaimana prinsip mulia kebebasan beragama telah bersinggungan dengan kebangkitan nasionalisme Kristen, yang menimbulkan ancaman signifikan terhadap demokrasi dan hak asasi manusia di dalam negara tersebut. Meskipun Konstitusi menekankan kebebasan individu, kemunculan nasionalisme Kristen telah memicu narasi yang memprivilesekan identitas agama tertentu di atas yang lain, sehingga merongrong prinsip-prinsip dasar kesetaraan dan pluralisme. Melalui analisis konteks historis, kerangka hukum, dan dinamika sosial-politik kontemporer, artikel ini mengeksplorasi interaksi kompleks antara kebebasan beragama, hak asasi manusia, dan merambahnya nasionalisme Kristen pada norma-norma demokrasi. Artikel ini mengeksplorasi tantangan yang ditimbulkan oleh situasi paradoksal yang ditimbulkan dan menekankan perlunya upaya yang mendesak untuk melindungi baik kebebasan beragama maupun hak asasi manusia dalam kerangka demokrasi Amerika Serikat. Kata-kata Kunci: Kebebasan beragama, Konstitusi AS, Nasionalisme Kristen, Demokrasi, Hak asasi manusia, Pluralisme, Dinamika sosial-politik.